The net effect of smoking on healthcare and welfare costs. A cohort study - Tiihonen, Jari (BMJ Publishing Group, 2012)
OBJECTIVE: To study the net economic effect of smoking on society. DESIGN: Prospective cohort study. SETTING: Eastern Finland. PATIENTS: We studied mortality, paid income and tobacco taxes, and the cumulative costs due to pensions and medical care among tobacco smoking and non-smoking individuals in a 27-year prospective cohort study of 1976 men from Eastern Finland. These individuals were 54–60 years old at the beginning of the follow-up. MAIN OUTCOME MEASURES: The net contribution of smoking versus non-smoking individuals to public finance balance (euros). RESULTS: Smoking was associated with a greater mean annual healthcare cost of €1600 per living individual during follow-up. However, due to a shorter lifespan of 8.6 years, smokers’ mean total healthcare costs during the entire study period were actually €4700 lower than for non-smokers. For the same reason, each smoker missed 7.3 years (€126 850) of pension. Overall, smokers’ average net contribution to the public finance balance was €133 800 greater per individual compared with non-smokers. However, if each lost quality adjusted life year is considered to be worth €22 200, the net effect is reversed to be €70 200 (€71.600 when adjusted with propensity score) per individual in favour of non-smoking. CONCLUSIONS: Smoking was associated with a moderate decrease in healthcare costs, and a marked decrease in pension costs due to increased mortality. However, when a monetary value for life years lost was taken into account, the beneficial net effect of non-smoking to society was about €70 000 per individual.